Biomechanical characteristics, patient preference and activity level with different prosthetic feet: A randomized double blind trial with laboratory and community testing. Issue 1 (2nd January 2015) - U. Raschke, Silvia; S. Orendurff, Michael; Mattie, Johanne L.; Kenyon, David E.A.; Jones, O. Yvette; Moe, David; Winder, Lorne; Wong, Angie S.; Moreno-Hernández, Ana; Highsmith, M. Jason; J. Sanderson, David; Kobayashi, Toshiki
Abstract: Providing appropriate prosthetic feet to those with limb loss is a complex and subjective process influenced by professional judgment and payer guidelines. This study used a small load cell (Europa™) at the base of the socket to measure the sagittal moments during walking with three objective categories of prosthetic feet in eleven individuals with transtibial limb loss with MFCL K2, K3 and K4 functional levels. Forefoot stiffness and hysteresis characteristics defined the three foot categories: Stiff, Intermediate, and Compliant . Prosthetic feet were randomly assigned and blinded from participants and investigators. After laboratory testing, participants completed one week community wear tests followed by a modified prosthetics evaluation questionnaire to determine if a specific category of prosthetic feet was preferred. The Compliant category of prosthetic feet was preferred by the participants ( P =0.025) over the Stiff and Intermediate prosthetic feet, and the Compliant and Intermediate feet had 15% lower maximum sagittal moments during walking in the laboratory ( P =0.0011) compared to the Stiff feet. The activity level of the participants did not change significantly with any of the wear tests in the community, suggesting that each foot was evaluated over a similar number of steps, but did not inherently increase activity. This is the first randomized double blind study in which prosthetic users have expressed a preference for a specific biomechanical characteristic of prosthetic feet: those with lower peak sagittal moments were preferred, and specifically preferred on slopes, stairs, uneven terrain, and during turns and maneuvering during real world use.